Interorganizational Knowledge Networks, R&D Alliance Networks, and Innovation Capability: A Multilevel Network Perspective - Yan Zhao; Xiao Han; Xiaoran Yang; Zheng Li (Complexity)
R&D alliances and knowledge networks are vital to the innovation process. Based on the multilevel network approach, our study comprehensively investigates several knowledge attributes of interorganizational knowledge networks and explores how R&D alliance networks are relevant for the relationship between knowledge attributes and organizational innovation capability. Samples in our research include 86 cliques from 2010 to 2015 in five Chinese high-tech industries’ R&D alliance networks. Results from the negative binomial regression model show that different knowledge attributes show a distinct effect on organizational innovation capability, including linear relationship, inverted U-shaped curve relationship, and inverted S-shaped curve relationship. Besides, our results identify that the central position within R&D alliance networks plays a limited role in the relationship between knowledge attributes and organizational innovation capability. Our findings could be used to help organizations sort out their knowledge attributes of knowledge bases, come to understand the impact of the interaction between the interorganizational knowledge network and R&D alliance network on the organizational innovation capability, and then make a targeted strategy to carry out innovation activities.